The relationship between reflective ability and professional identity: the mediating effect of self-directed learning and self-efficacy for junior clinical nurses - Lijie Huang; Xiangsheng Zhang; Feijie Wang; Songbo Zhang; Xiaoxia Chang; Yinping Chu; Lu Wang; Wenwen Jia; Beibei Zhang (BMC, 2024)
Abstract Background Nursing is crucial for delivering healthcare services; however, nursing shortages pose a significant global challenge, which the high turnover rate of junior nurses is expected to exacerbate. Enhancing nurses' professional identities is likely to be an effective strategy for reducing turnover rates. Methods We recruited 865 junior clinical nurses from three tertiary hospitals in Henan Province, China. The participants completed a demographic questionnaire along with the Reflective Ability Scale for Clinical Nurses, the Nursing Profession Self-efficacy Scale, the Nursing Staff Self-learning Ability Evaluation Scale, and the Professional Identity Scale for Nurses. The relationships between reflective ability, self-directed learning, self-efficacy, and professional identity were evaluated using SPSS26.0, with PROCESS version 3.5 used to construct a chain-mediation model. Results Positive correlations were found between reflective ability, self-directed learning, self-efficacy, and professional identity. Chain mediation model analysis showed that reflective ability, self-directed learning, and self-efficacy directly and positively affected professional identity (β = 0.22, β = 0.30, β = 0.66, all p < 0.001). Self-directed learning and self-efficacy exerted a significant chain mediating effect between reflective ability and professional identity (95% confidence interval [CI]: 0.06-0.13). The total effect of reflective ability on the professional identity of clinical nurses was 0.51 (p < 0.001, 95%CI: 0.42-0.59), the direct effect was 0.22 (p < 0 0.001, 95%CI: 0.14-0.29), and the indirect effect was 0.29 (p < 0.001, 95%CI: 0.22-0.37). Conclusion Self-directed learning and self-efficacy partially mediated the relationship between reflective ability and professional identity. Multifaceted strategies targeted at enhancing reflective ability, self-directed learning, and self-efficacy are recommended to improve junior clinical nurses' professional identities.